Didactic activities for the development of English speaking skills in students of seventh grade egb at ciudad de Salinas school, Santa Rosa, Salinas, province of Santa Elena. School year 2014-2015. - Borbor Arreaga, Edith De Las Nieves (2015)
Nowadays, the advance of education is very significant; therefore this is innovation to teach a quality and warmth education. Even when the didactic activities are enjoyable, they influence in the teaching and are of great importance to promote the interest and motivation for the development of English speaking skills. For this reason this research work has the aim to develop the skills of speech to seventh grade students of Ciudad de Salinas School through entertaining didactic activities. The author has accomplished a survey to twenty two students of school; they have answered thirteen questions related to the use of didactic activities. The results show that the use of didactic activities is important to develop the speaking in English in the daily life and the future. Furthermore, it has been found that didactic activities like: telling stories, puppets, spelling bee, oral presentation, role-play among others are the complement to learn how to speak English.